2013
DOI: 10.3329/bjpbg.v20i1.17015
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC VARIATION, CORRELATION AND SELECTION INDICES IN ADVANCED BREEDING LINES OF RICE (Oryza sativa L.)

Abstract: Forty advanced breeding lines of rice were studied during T Aman season (rainfed ecosystem) for finding out selection indices, variability and character association for grain yield and its components. All the tested characters were found showing significant variation. The highest genotypic, environmental and phenotypic variances were found in filled grains/panicle followed by plant height. High heritability associated with high genetic advance were obtained in panicles/hill, plant height, filled grains/panicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…These results indicated the feasibility of selection for these traits. Our results are in accordance with those obtained by Habib et al (2007), Ferdous et al (2010), Fellahi et al (2018), and Rasha (2020. The reduction in PCV and GCV values in the advanced generation (F3, F4, and F5) may be due to a reduction in genetic variability and heterozygosity as a result of using different selection procedures that exhausted a major part of variability.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results indicated the feasibility of selection for these traits. Our results are in accordance with those obtained by Habib et al (2007), Ferdous et al (2010), Fellahi et al (2018), and Rasha (2020. The reduction in PCV and GCV values in the advanced generation (F3, F4, and F5) may be due to a reduction in genetic variability and heterozygosity as a result of using different selection procedures that exhausted a major part of variability.…”
Section: Discussionsupporting
confidence: 91%
“…When single trait selection is practiced and the correlation of that trait with others is high and unfavorable, an undesirable correlated response may occur for those traits not considered in selection criteria (Bos and Caligari, 1995;Patel et al, 2019). In order to get through these obstacles in a multi-trait approach, breeders are concentrating on additional traits that can be employed concurrently with or independently of yield (Habib et al, 2007). A breeding program's likelihood of success is increased by simultaneously selecting features that are important from an economic perspective (Sayd et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Variance components and genetic gains are routinely estimated to evaluate the effectiveness of the selection method applied to certain breeding objectives [48]. Previous studies reported larger genetic gains from simultaneous selection than single-trait selection in several crops such as rice [49], sugarcane [50], wheat [51], and maize [26]. In our study, the realized gain of both ORSI and selection index was assumed as the percent average differences between selected means and grand means.…”
Section: Genetic Gains Reflect the Effectiveness Of Simultaneous Selectionmentioning
confidence: 99%
“…Selection index is commonly used in grain crop for selecting efficient combination characters and improvement of crop based on that combination index. Selection index was reported by Yang et al (1991) in wheat, Habib et al (2007) in rice and Bashar et al (2015) in egg plant.…”
mentioning
confidence: 91%